Introduction to software engineering - Leach, Ronald J. (CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an Informa business, 2016)
"Software engineering lies at the heart of the computer revolution. Software is used in automobiles, airplanes, and many home appliances. As the boundaries between the telecommunications, entertainment, and computer industries continue to blur in multimedia and networking, the need for software will only increase, and software will become increasingly complex. Introduction to Software Engineering gives your students the fundamentals of this growing and rapidly changing field. The book highlights the goals of software engineering, namely to write programs that have all the following attributes: efficient, reliable, usable, modifiable, portable, testable, reusable, maintainable, compatible and correct. The nine chapters cover topics that include project management, defining requirements, software design, coding, testing and integration, delivery and installation, documentation, maintenance, and research issues. The author uses a hybrid approach, combining object-oriented technology and classical programming techniques to solve computing problems. He also places a strong emphasis on Internet technology and resources. A simple, but non-trivial, running example illustrates all stages of the software engineering process. In addition, where applicable, he covers the impact of Internet technology."- Resumé vydavatel
Keywords: softwarové inženýrství; software engineering; učebnice; elektronické knihy; textbooks; electronic books